Pengetahuan ibu tentang pneumoniapada balita mengalami peningkatan setelah diberikan penyuluhan - Normalita Puspitasari; Enny Fitriahadi (JHeS (Journal of Health Studies), 2018)
The objective of the research was to identify the influence of counseling and educating program on the mothers’ knowledge about pneumonia in toddler The method of the research was Pre experiment with cross sectional time approach. The design of the research was one group pre-test post-test design. Total Sampling was applied, and the samples of the research were 45 people. The Data were collected by questionnaire. The data were analyzed by Wilcoxon match pairs test. The statistical test resultobtained p value 0.000 (p value lower than 0.05). There was an effect of counseling and educating program to the mothers’ knowledge about pneumonia in toddler at Matahari Maternal Health Center Sariharjo village, the working area of Ngaglik II Primary Health Care.